PERAN KLUB MOTOR DALAM PEMBENTUKAN PERILAKU BERKENDARA YANG AMAN (SAFETY RIDING) - ROYAN PRAYUDI (Departemen Sosiologi Universitas Sumatera Utara, 2013)
Transport is one of the most important elements in human life and in its development. Transportation has become one of the most basic human needs, all human affairs today can not be separated with the transport. To support the transportation needs of its users awareness to always put safety and riding motorcycle club as one of the social groups that are in the community can be made in one of the means to campaign for Safety Riding. This type of research conducted in this research is descriptive qualitative approach. What this study were in secretarial STIC at Setia Budi Street No. 5 with the unit of analysis is the motorcycle club members who attend club activities STIC and understood the Safety Riding. From the results of research conducted to informants in the know that the members of STIC gain knowledge Riding Safety Safety is always campaigning for riding to the public. Clubs also provide sanctions for members who violate Safety Ridding Keywords: Transportation, Safety riding, Motorcycle club